P258 3D printed models in fistulising perianal Crohn's as a clinical tool boost education with patients and trainees. (16th January 2018) - Sahnan, K; Adegbola, S O; Tozer, P J; Gupta, A; Warusavitarne, J; Faiz, O D; Hart, A L; Phillips, R K; Lung, P F
Abstract: Background: Surgical understanding of complex fistula anatomy is usually mediated through interactions with radiologists through multidisciplinary meetings. However, not all surgeons review imaging with radiologists and it is not always possible in particular settings (e.g. clinic or theatre). Alternative communication of these scans maybe useful. 3D printing provides a more realistic model that can aid surgical understanding, improve trainee education and empower patient communication. We describe our experience of 3D printing for complex tertiary referrals. Methods: Standard axial T2-weighted Spectral Attenuated Inversion Recovery (SPAIR) MRI sequences were acquired. Digital imaging and communications in medicine (DICOM) images of the MRI sequences were retrieved from the picture archiving and communication system (PACS) system. DICOM images were imported into validated open-source segmentation software. A specialist consultant gastrointestinal radiologist performed segmentation of the fistula tract, the internal and the external sphincters. The segmented files were exported as STereoLithography (STL) files. We used Cura (Ultimaker Cura 3.0.4) to prepare the files for printing on an Ultimaker 3 Extended 3D printer. Results: Two cases of perianal Crohn's fistula are shown below in Table 1 that include two axial slices from the conventional 2D MRI scan: original and segmented; and the 3D printed models. Anatomical components are displayed in different colours (Red: Fistula Tract; Green: External Anal Sphincter (EAS) and Levator Plate; Blue: Internal Anal Sphincter (IAS) and Rectum). Figure 1, orientates the model in anatomical positions. In both examples, complex fistulas are demonstrated to highlight the ability to the technique to enhance the comprehension of complex fistula referred to our tertiary institution. Conclusions: Due to the complexity of tracts and the intimacy with the anal sphincter, perianal fistulas are an example of a topic that is not only hard to understand but also hard to teach. Such topics lend themselves to 3D printing very well and also be taken away by patients at the end of their consultation. Subsequent work will focus on how to make these models more interactive, such as being able to take them apart to understand, for example, complexity the intersphincteric space and the orientation of the internal opening.